2014
DOI: 10.1186/1756-0500-7-482
|View full text |Cite
|
Sign up to set email alerts
|

A study of snake bite among children presenting to a paediatric ward in the main Teaching Hospital of North Central Province of Sri Lanka

Abstract: BackgroundSnake bite is a common problem in the North Central province of Sri Lanka. Common krait (Bungarus careuleus), Ceylon krait (Bungarus ceylonicus), Cobra (Naja naja), Russell’s viper (Daboia russelii), Saw-scaled viper (Echis carinatus) and Hump-nosed pit viper (Hypnale hypnale) are the six species of venomous land snakes in Sri Lanka. A significant number of adults and children are bitten by snakes every year. However, the majority of research studies done in Sri Lanka and other countries show adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
(44 reference statements)
8
19
2
Order By: Relevance
“…The most frequently bitten site in our study was the lower extremity (85.2%). Similar observations have been made in other studies [12,14]. But the study done by Aktar F [15] on snake bite envenomation in 151 children, most common location of bite was right forearm in 61.6% of children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most frequently bitten site in our study was the lower extremity (85.2%). Similar observations have been made in other studies [12,14]. But the study done by Aktar F [15] on snake bite envenomation in 151 children, most common location of bite was right forearm in 61.6% of children.…”
Section: Discussionsupporting
confidence: 89%
“…The epidemiological character in our study showed that more common victims in children were males when compared to females. Similar observation was made by Karunanayake RK [14] in a study on 54 children with snake bite envenomation.…”
Section: Discussionsupporting
confidence: 84%
“…Studies on pediatric snake bite victims were limited, however similar observation was seen by Kshirsagar et al and Karunanayakeet al with 89% and 48% children more than 5 yearsrespectively 5,6 . The mean age of 10.7 years is reported by Schulte et al 6 .Larger proportion of the victims were males (61.4%) and the male to female ratio was 1.6:1. This correlates with various studies with higher incidence in males.…”
Section: Discussionmentioning
confidence: 76%
“…In a study conducted by Karunanayake et al in Sri Lanka highest numbers of bites (48%) were in the range of ages 6-12 years. 5 Maximum number of snake bite occurred during the months of June (24%) and July (16%), together constituting 40% of the total. Another peak was observed during October (12%).…”
Section: Discussionmentioning
confidence: 99%